APPLICATION OF PROJECT BASED LEARNING MODELS TO IMPROVE ECOLITERACY OF ELEMENTARY SCHOOL STUDENTS THROUGH URBAN FARMING ACTIVITIES - Hana Sakura Putu Arga (STKIP Siliwangi, 2018)
This research is motivated by the concern of the author towards students of Public Elementary School 038 Kiaracondong Bandung who lack awareness in doing greening resulting in an arid and poorly maintained school environment. The purpose of this research is to improve the ecoliteracy of students so that they are more sensitive to the importance of the green environment so that they want to do a greening movement even though they have limited space. This research was conducted with the Classroom Action Research (PTK) method using the design of Kemmis and Taggart (2001) on grade IV students of SDN 038 Kiaracondong Bandung. The results of research conducted in 3 cycles with 12 meetings showed an increase in ecoliteracy in students towards greening the space indicated by behavior, one of which was; 1) students grow awareness to reforest on school land despite limited space; 2) students plant ornamental plants and vegetables with pots that come from processed waste; 3) students are responsible for caring for the plants well; 4) students take care of flowers and give fertilizer regularly; 5) students grow creativity in processing plastic waste into flower pots; 6) students are able to distinguish between types of waste. Through urban farming activities students experience a process of improving ecoliteracy which is not only applied in the school environment but also in the home environment.  Keywords:         Project Based Learning, Ecoliteracy, Urban Farming